Academic Leadership of School Administrators Affects the Effectiveness of Secondary School Curriculum Management under the Secondary Educational Service Area Office Bangkok 1 - Sangchaisriyakul, Yukhonthorn; Siththada, Thada (Interdisciplinary Academic and Research Journal, 2022)
Successful educational establishments often have managers capable of facilitating, supporting, and leading innovations in the school and driving educational reforms, especially in teaching and learning management, it requires leaders who are knowledgeable in academics. Therefore, this study aimed to 1) the levels of academic leadership of school administrators that affect the effectiveness of secondary school curriculum management 2) the levels of the effectiveness of secondary school curriculum management, and 3) academic leadership of school administrators affects the effectiveness of secondary school curriculum management. The sample of this study were administrators and teachers in schools under the Secondary Educational Service Area Office Bangkok 1 in the academic year 2021, totaling 354 people. The instrument was a survey with a reliability of .90. Data analysis was using percentages, means, standard deviations, Pearson product-moment correlation coefficients, and Stepwise Multiple Regression Analysis. The study found that; 1) the overall levels of academic leadership of school administrators were at a high level, 2) the overall levels of the effectiveness of secondary school curriculum were at a high level, and 3) The relationship between the academic leadership of school administrators and the effectiveness of secondary school curriculum management found that in terms of setting vision, mission, goals and creating a learning atmosphere, there was a low positive correlation. It was not statistically different. There was a correlation coefficient between .093 and .061. In terms of learning management and teaching supervision, there was a statistically significant high-level positive correlation at the .01 level. It has a correlation coefficient between .773 and .875. The predictive power was 96.60 percent, and statistical significance was at the .01 level.